2023
DOI: 10.5009/gnl220202
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sulfate Solution Is as Effective as Polyethylene Glycol with Ascorbic Acid in a Split Method for Bowel Preparation in Patients with Inactive Ulcerative Colitis: A Randomized, Multicenter, and Single-Blind Clinical Trial

Abstract: Background/Aims: Low-volume preparations for colonoscopy are gaining attention for their higher acceptability. However, the efficacy and safety of oral sulfate solution (OSS) preparations in patients with ulcerative colitis (UC) has not been well known. Therefore, we aimed to compare OSS and 2-L polyethylene glycol with ascorbic acid (PEG+Asc) for bowel preparation in inactive UC.Methods: A multicenter, randomized, single-blind study was conducted at six tertiary referral hospitals in Korea. Outpatients with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The safety and efficacy profile was comparable. Lee et al [ 20 ] also reported a similar efficacy and safety profile (even considering changes in serum electrolytes) between novel oral sulphate solution and PEG-ascorbate in 92 patients with inactive ulcerative colitis.…”
Section: What Profile Do Non-peg Solutions Have In Ibd?mentioning
confidence: 86%
“…The safety and efficacy profile was comparable. Lee et al [ 20 ] also reported a similar efficacy and safety profile (even considering changes in serum electrolytes) between novel oral sulphate solution and PEG-ascorbate in 92 patients with inactive ulcerative colitis.…”
Section: What Profile Do Non-peg Solutions Have In Ibd?mentioning
confidence: 86%
“…To the Editor: We extend our congratulations on the study conducted by Lee et al, 1 which demonstrated the efficacy of oral sulfate solution (OSS) administration in patients with ulcerative colitis (UC) based on the results of colonoscopic procedures. While there have been numerous reports within the scientific community regarding the usefulness and efficiency of OSS in patients with UC, this study is the first publication in the literature to emphasize the advantages of such findings.…”
mentioning
confidence: 93%